2020
DOI: 10.1002/jcp.30007
|View full text |Cite
|
Sign up to set email alerts
|

The overview and perspectives of biosensors and Mycobacterium tuberculosis: A systematic review

Abstract: Tuberculosis (TB) is referred to as a "consumption" or phthisis, which has been a fatal human disease for thousands of years. Mycobacterium tuberculosis (M. tb) might have been responsible for the death of more humans than any other bacterial pathogens. Therefore, the rapid diagnosis of this bacterial infection plays a pivotal role in the timely and appropriate treatment of the patients, as well as the prevention of disease spread. More than 98% of TB cases are reported in developing countries, and due to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 103 publications
(140 reference statements)
0
9
0
Order By: Relevance
“…The lowest LOD reported from an electrochemical DNA biosensor was based on graphene-modified iron-oxide chitosan with 0.9 fg/mL. 68 Moreover, Pourmir et al reported an LOD value for TB 10 4 CFU/mL, 44 whereas the designed sensor in our study obtained 10 3.82 CFU/mL, which is considered a good value.…”
Section: Resultsmentioning
confidence: 44%
“…The lowest LOD reported from an electrochemical DNA biosensor was based on graphene-modified iron-oxide chitosan with 0.9 fg/mL. 68 Moreover, Pourmir et al reported an LOD value for TB 10 4 CFU/mL, 44 whereas the designed sensor in our study obtained 10 3.82 CFU/mL, which is considered a good value.…”
Section: Resultsmentioning
confidence: 44%
“…FC is an optical technique used for cell counting and the detection of biomarkers One of the leading causes contributing to the global increase in AMR is the empirical use of broad-spectrum AMs in clinical and veterinary practices [18]. For the early detection of microorganisms, for the prevention of diseases and spread of AMR, it is essential to have well-equipped laboratories specialized in the diagnosis of infections [19]. It is difficult to meet this requirement in developing countries because of the lack of funds, shortage of trained personnel, and lack of the required infrastructures.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…The use of chemosensor and biosensor technology is an alternative approach which possesses technical simplicity, low cost, short analysis time, easy operation, and hold exceptional promise for providing critical information for real-time data collection and simultaneous measurements of multiple analytes (multiplexing) within a single device. In general terms, chemosensors are devices that measure the signal produced by a chemical reaction whereas biosensors can be defined as "compact analytical devices incorporating a biological or biologically derived sensing element either integrated within or intimately associated with a physicochemical transducer" [18,19,[51][52][53][54][55][56][57][58].…”
Section: Antimicrobial Resistancementioning
confidence: 99%
See 2 more Smart Citations